Psychodynamic incidents in teaching: Researching relational aspects of classroom practice (UCL Press, 2019)
For those working in the relatively new field of psychosocial studies, the action of psychodynamic phenomena in day-to-day life is uncontroversial as these phenomena are at work both in clinical settings and in normal life outside the clinical frame. If this is indeed the case, then they must also be at play in everyday classrooms. But to what degree, and to what effect - and how can we create data exploring these issues? This article is the result of a doctoral study that looks at these issues. It explores the methodological and ethical complexities around investigating intimate psychodynamic events experienced in the public context of the school; it presents some extracts from the data constructed, exploring the intersection between narrative methods, autoethnography and psychoanalytic inquiry. This article concludes with some suggestions as to ways that teachers and researchers might continue to explore such psychodynamic incidents.